PENGARUH METODE PEMBELAJARAN ENRICHMENT MODEL RENZULLI TERHADAP KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK DALAM PEMBELAJARAN SEJARAH KELAS XI IPS - Herlinda Ika Putri; Sumiyatun Sumiyatun (Swarnadwipa, 2019)
The purpose of this study was to determine the effect of Renzulli's Enrichment learning method on students' critical thinking skills in learning history of class XI IPS. This research was conducted at SMA N 1 Purbolinggo. The type of research used is quasi experiment. In this study the design (design) used is Nonequivalent Control Group Design. Conducting research, namely research preparation, test trials, pre-test treatment, learning activities, and post-test administration. The results of the study are as follows: (1) There is a difference in the average historical learning outcomes of students who use the Renzulli Model Enrichment Learning Method ( ???????? = 77.5294) is greater with a range value of 6.8529 than the average using the discussion method ̅???????? = 70.6765), (2) The average results of students' critical thinking skills in history learning using the Renzulli Model Enrichment Learning Method ( ???????? = 77.5294) is greater with a range value of 6.8529 than the average using the discussion method ̅???????? = 70.6765). Thus it can be concluded that the Renzulli Model Enrichment Learning Method has a significant influence on students' critical thinking skills in history learning.